Blessing or curse? The effects of transparency on the European Commission's success at the international ACTA negotiations - Josef Eibauer (Freie Universität Berlin, Center for International Political Economy, 2012)
The present study tries to investigate on the dynamics between the level of transparency of international treaty negotiations and the success of European Commission negotiators in achieving their particular political interests. Drawing upon an alternated version of Robert Putnam's two-level game approach, two distinct hypotheses are established. First, a low level of transparency of international treaty negotiations increases the amount of gains available to European Commission negotiators at the international level. Second, a low level of transparency of international treaty negotiations decreases the likelihood of ratification at the non-international level. These hypothesis are tested against the case of the international Anti-Counterfeiting Trade Agreement (ACTA) negotiations and the subsequent ratification procedure that took place between the years 2005 and 2012. Empirically, it can be confirmed that the ACTA talks' low level of transparency detached the usually intertwined international, supranational, and domestic negotiation levels and thus increased the political leeway available to the Commission, leading to a treaty text that reflected its tough stance on intellectual property rights regulation. However, the low level of transparency also resulted in the Commission's lack of information about the true nature of negotiation outcomes that were acceptable to both the public and parliamentary majorities. Indeed, following a lively campaign against the treaty that was predominantly coordinated via the internet and social networks, ACTA ultimately failed ratification both on Member State and Community levels. In a nutshell: When the debated issues are controversial and salient to the public, the European Commission is likely to fail reaping the benefits of international negotiation secrecy.
Keywords: 330